Effects of intercropping on the life cycle of the turnip root fly (Delia floralis) - Björkman, Maria (2007)
The turnip root fly (Delia floralis) is a pest insect in the northern temperate regions of the world. If uncontrolled, it can cause severe problems in the production of brassica crops. This thesis examines how intercropping of cabbage (Brassica oleracea) and red clover (Trifolium pratense) affects the different life cycle stages of D. floralis. Such knowledge about the mechanisms involved is needed for developing intercropping systems with optimal pest reduction. A field trial was performed in Umeå, northern Sweden (63º45’N; 20º15’E), to study the effects of intercropping on D. floralis oviposition behaviour, and the impact of predators and parasitoids on D. floralis in the field. Intercropping was found to reduce D. floralis oviposition compared with monoculture. Furthermore, analysis of the spatial distribution of eggs within plots showed that the difference in egg numbers was greatest close to the border between the cultivation systems. This indicates that the effect of intercropping can be enhanced if D. floralis is provided with an alternative oviposition site. Natural enemies, in this case mainly predators, significantly reduced the final pupal numbers of D. floralis but this effect did not differ between the cultivation systems. However, the study showed that it is possible to retain the predation pressure in intercropped systems despite lower predator activity-densities and D. floralis egg numbers. A greenhouse experiment was performed to investigate effects of intercropping on development of D. floralis at different larval and intercropping densities and to analyse different aspects of host plant quality in the same system. It was found that D. floralis pupal weight decreased in response to both intercropping and larval density. This impaired larval development is likely to be explained by changes in host plant quality, which included decreased biomass, lower root nitrogen levels, higher root fibre content and altered glucosinolate concentrations. Information on plant responses to herbivory in ...